2020
DOI: 10.21203/rs.3.rs-60899/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LDL-C/HDL-C is Associated With Ischaemic Stroke in Patients With Non-Valvular Atrial Fibrillation: A Case-Control Study

Abstract: Background This study explored relationships between low-/high-density lipoprotein cholesterol ratio (LDL-C/HDL-C) and other clinical indicators and ischaemic stroke (IS) in non-valvular atrial fibrillation (NVAF) patients in Xinjiang, which could provide a theoretical and therapeutic basis for patients with NVAF. Methods NVAF patients who were admitted to 10 medical centres across Xinjiang were divided into the stroke (798 patients) and control (2671 patients) groups according to whether acute IS occurred. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…These lipoproteins have been recommended for screening people with a high risk of NAFLD in clinical practice [18]. Recently, some studies have pointed out that the LDL/HDL cholesterol ratio can simultaneously evaluate LDL cholesterol and HDL cholesterol, and its performance in predicting the risk of cardiovascular and cerebrovascular metabolic-related diseases is better than that of a single lipoprotein [19][20][21]. At present, there are no research data on the association between NAFLD and the LDL/HDL cholesterol ratio.…”
Section: Introductionmentioning
confidence: 99%
“…These lipoproteins have been recommended for screening people with a high risk of NAFLD in clinical practice [18]. Recently, some studies have pointed out that the LDL/HDL cholesterol ratio can simultaneously evaluate LDL cholesterol and HDL cholesterol, and its performance in predicting the risk of cardiovascular and cerebrovascular metabolic-related diseases is better than that of a single lipoprotein [19][20][21]. At present, there are no research data on the association between NAFLD and the LDL/HDL cholesterol ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that peripheral vascular atherosclerosis severely affects the most signi cantly prediction-related for deadliness and death of CVD. It has been reported that when the conventional lipid parameters triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and total cholesterol (TC) remain apparently normal, other lipids such as lipid ratios, including TC/HDL-C, LDL-C/HDL-C, TG/HDL-C, and non-HDL-C/HDL-C are the diagnosticate alternatives that have been shown to predict the risk of a cardiovascular event [3][4][5] . Studies have shown LDL-C that plays a key role in the pathogenesis of AS.…”
Section: Introductionmentioning
confidence: 99%